HUBUNGAN ANTARA KEMATANGAN KARIER DENGAN QUARTER LIFE CRISIS PADA PEKERJA - Imamah, Fa’iqotul; Satiningsih, Satiningsih (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2025)
The quarter-life crisis is a psychological phenomenon commonly experienced by individuals aged 18–29, characterized by anxiety, confusion, and pressure in making life decisions, particularly regarding career. One factor influencing this condition is career maturity, defined as the readiness to plan and make career decisions appropriate to one’s developmental stage. This study aimed to examine the relationship between career maturity and quarter-life crisis among 115 employees at a business entity in Lamongan Regency. Using a quantitative approach with a correlational design, the study identified the strength and direction of the relationship between variables without manipulation. The instruments were a career maturity scale (Donald Super) and a quarter-life crisis scale (Robbins & Wilner), with validity tested using corrected item–total correlation and reliability assessed via Cronbach’s alpha. The results revealed a significant negative relationship (r = -0.428, p < 0.05) with r² = 18.3%, indicating that career maturity explains 18.3% of the variance in quarter-life crisis. This finding fills a research gap that has predominantly focused on university students by highlighting a worker population facing real-world career challenges. Career maturity was shown to act as a protective factor against quarter-life crisis and provides a basis for developing workplace career mentoring programs. ABSTRAK Quarter life crisis adalah fenomena psikologis yang umum dialami individu usia 18–29 tahun, ditandai kecemasan, kebingungan, dan tekanan dalam menentukan arah hidup, khususnya karier. Salah satu faktor yang memengaruhinya adalah kematangan karier, yakni kesiapan merencanakan dan mengambil keputusan karier sesuai tahap perkembangan. Penelitian ini bertujuan menguji hubungan antara kematangan karier dan quarter life crisis pada 115 pekerja di sebuah badan usaha di Kabupaten Lamongan. Menggunakan pendekatan kuantitatif dengan desain korelasional, penelitian ini mengidentifikasi kekuatan dan arah hubungan antarvariabel tanpa manipulasi. Instrumen yang digunakan adalah skala kematangan karier (Donald Super) dan skala quarter life crisis (Robbins & Wilner), dengan validitas diuji melalui corrected item–total correlation dan reliabilitas melalui Cronbach’s Alpha. Hasil menunjukkan hubungan negatif signifikan (r = - 0,428, p < 0,05) dengan r² = 18,3%, yang berarti kematangan karier menjelaskan 18,3% variasi quarter life crisis. Temuan ini mengisi kesenjangan penelitian yang sebelumnya berfokus pada mahasiswa, dengan menyoroti populasi pekerja yang menghadapi tantangan nyata di dunia kerja. Kematangan karier terbukti berperan sebagai faktor protektif terhadap quarter life crisis dan menjadi dasar pengembangan program pendampingan karier di lingkungan kerja.